2008
DOI: 10.1093/schbul/sbn100
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between IQ, Memory, Executive Function, and Processing Speed in Recent-Onset Psychosis: 1-Year Stability and Clinical Outcome

Abstract: Studies commonly report poor performance in psychotic patients compared with controls on tasks testing a range of cognitive functions, but, because current IQ is often not matched between these groups, it is difficult to determine whether this represents a generalized deficit or specific abnormalities. Fifty-three first-episode psychosis patients and 53 healthy controls, one-to-one matched for sex, age, and full-scale current IQ, were compared on Wechsler Adult Intelligence Scale (WAIS) subtests representing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
71
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 51 publications
17
71
0
1
Order By: Relevance
“…When investigating the clinical relevance of our cognitive findings we found poorer cognitive ability, specifically reasoning and problem solving and social cognition at illness onset, to predict greater negative symptom severity four years later. Longitudinally, performance on a variety of cognition domains at illness onset, such as processing speed, IQ, working memory and verbal learning, have been found to relate to the course of negative symptom severity (Leeson et al, 2010;Carlsson et al, 2006;Bora and Murray, 2013;González-Ortega et al, 2013). Taken together, these data support cognition at illness onset as a potential predictive indicator of illness course; however, there is yet heterogeneity as to which exact cognitive domain which relates to negative symptom severity.…”
Section: Discussionmentioning
confidence: 92%
“…When investigating the clinical relevance of our cognitive findings we found poorer cognitive ability, specifically reasoning and problem solving and social cognition at illness onset, to predict greater negative symptom severity four years later. Longitudinally, performance on a variety of cognition domains at illness onset, such as processing speed, IQ, working memory and verbal learning, have been found to relate to the course of negative symptom severity (Leeson et al, 2010;Carlsson et al, 2006;Bora and Murray, 2013;González-Ortega et al, 2013). Taken together, these data support cognition at illness onset as a potential predictive indicator of illness course; however, there is yet heterogeneity as to which exact cognitive domain which relates to negative symptom severity.…”
Section: Discussionmentioning
confidence: 92%
“…In early illness stages, however, attentional set-shifting ability appears to be preserved or only minimally affected. A number of studies have found no differences between FEP patients and healthy controls on the IED task [12,[38][39][40], and a small study of pre-psychotic individuals also found no impairment in attentional set-shifting ability [41]. These findings are interesting when considered in the context of developmental trajectories of these tasks, as discussed below.…”
Section: Evidence For Cognitive Decline In Early Psychosismentioning
confidence: 82%
“…[3] Leeson and his colleagues in his research also get the same results that intelligence significantly correlated with cognitive function, especially memory and executive function. [4] Beilen et al, in a study also get the same result, namely a clear link between the level of intelligence and memory function, attention and executive function of the cognitive function. According to him, intelligence and cognitive function may be difficult to distinguish.…”
Section: Resultsmentioning
confidence: 54%